Effect of water stress and elevated temperature on hypoxia and cell death in the mesocarp of Shiraz berries. (18th July 2018) - Xiao, Z.; Liao, S.; Rogiers, S.Y.; Sadras, V.O.; Tyerman, S.D.
Abstract: Background and Aim: Berry shrivel during ripening is cultivar dependent and is correlated with berry cell death (CD). We hypothesised that under heat stress and water stress, regions of the pericarp in Shiraz berries would become hypoxic depending on berry porosity, and that this would induce CD. Methods and Results: We measured CD and [O2 ] across the pericarp in berries developed under the factorial combination of two thermal regimes (ambient and heated) and two irrigation regimes (irrigated and non‐irrigated) in the Barossa Valley, South Australia. Heating increased ambient temperature by 0.6°C for irrigated and 1°C for non‐irrigated vines but had no effect on water relations, while non‐irrigation decreased stomatal conductance and stem water potential. Non‐irrigation decreased berry [O2 ] and increased both CD and ethanol concentration relative to irrigation. An association was established between mesocarp [O2 ] and CD. Berry respiration and total berry porosity decreased during berry ripening, but relative locule air‐space measured by X‐ray micro‐computed tomography increased late in ripening. Heating had little or no effect on CD or [O2 ] but decreased berry porosity, which was not affected by irrigation. Conclusion: Water stress increased berry CD, which was associated with increased hypoxia. Significance of the Study: The association between berry [O2 ] and CD provides insights into berry ripening with implications for yield and berry flavour.